Religious Itineraries as the Driving Forces behind Sustainable Local Development in the Veneto? Towards a Proposal for Promoting an Unusual and Often “Subliminal” Form of Heritage: Sanctuaries and Minor Churches - Rizzo, Luca Simone; Rizzo, Raffaela Gabriella; Trono, Anna (Almatourism - Journal of Tourism, Culture and Territorial Development, 2013)
Religious sites/assets are reacquiring pre-eminence, partly in the role of mainsprings for local development: they are privileged witnesses to collective memory and depositories for symbolic, historical, cultural and spiritual values that they have contributed towards forging. These are essential keys for interpreting “places” and their evolution, as well as for studying their various facets and nuances in greater detail. In full knowledge of this, we are presenting here a study on the subject of cultural (and religious) itineraries as a determining element in territorial conservation and as an instrument for: a) promoting a type of tourism that is sustainable, alternative and aware, in which the approach towards “exploitation” changes (contributing towards not only the “consumption” of experiences, but also the enrichment of the tourist); b) highlighting the value of authenticity and contact with local culture, as well as promoting contextual elements that are highly distinctive. In line with the need to make better use of local religious heritage, we identified anchor sites (sanctuaries and minor churches) around which to develop further forms of (religious) tourism. We devised an itinerary some 300 km long that “expresses” the diverse environmental/cultural/gastronomic realities that have the sanctuaries at their centre. This itinerary and its sub-routes – created via GIS – cover the central and western parts of the Veneto, as well as the south of the Region. The main route connects the sites in an attempt to link the area under examination, thanks to a ring, to the ancient Via Romea (the subject of research and reclamation as a long distance route).